ADAPTASI SISWA SMA N 1 SURAKARTA DALAM PEMBELAJARAN GEOGRAFI DI TENGAH WABAH COVID-19 - Mukharomah, Chusnul Feby; Fitri, Affi Anisa; Nugraha, Arya Satria; Zidan, Fauzan; Amanda, Firda Oktavia; Sari, Madinda Puspita; Azizah, Novita Nur (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2020)
This research aim for know adaptation of geography learning student during covid-19 as well as close school during learning. this reseach is quantitative. source of the reseach is informan, place or event and document. questionnaire technique. the data analysis use statistic analysis descriptive. withdrawal of reports using reasoning from theoritical studies and discussion result. this reseach resulted adaptation effrot learning of geography during covid-19 which has been face to face teacher and students are now transformed to online or daring from house which is 100%. daring or online allow teacher and studens not to meet face to face make use of online aplication specific for study, mostly choose home learning application 3,36%. as for the obtsacles faced by student when doing online learning namely lack of consentration of student receiving material because the condution is not condusive of 70,20%, the are no assistan of 64,8%, and limited digital media at home to supprort online laerning of0,25%.